ELSA-Supported Blended Learning: Enhancing Vocational Students’ Speaking and Motivation - Wahyudin, Wahyudin; Bachtiar, Bachtiar; Zuhairi, Aminudin (Journal of English Language and Education, 2025)
Developing employability-ready English speaking skills remains challenging and persistent in Indonesian vocational schools across contexts. This mixed-methods study investigated the effectiveness of ELSA, an AI-driven speaking app, embedded in a four-week blended course with two weekly 90-minute sessions for 30 Grade-11 Agribusiness students. Surveys (validated), CEFR-aligned observations, and interviews examined gains in pronunciation, fluency, confidence, and motivation, and documented implementation factors. Results show marked improvement in prosody, articulation, and extended turns; learners reported higher confidence, autonomy, and sustained engagement driven by real-time feedback, progress tracking, and gamified tasks. Skills transferred to vocationally authentic performances (e.g., product descriptions, customer service, job-interview simulations). However, efficacy depended on device availability, stable connectivity, digital literacy, and teacher mediation; freemium limits also constrained practice. The study concludes that ELSA-supported blended learning offers a practical, scalable model to strengthen oral proficiency and motivation in vocational EFL programs, provided institutions ensure equitable access, teacher support, and curricular alignment.